Adaptation of a mobile app for early anxiety and depression intervention in university students in Chile: participatory study - Daniela Lira; Patricio Caviedes; Vania Martínez (BJPsych International, 2023)
The high prevalence of mental health problems among university students poses a challenge when developing effective interventions, with digital technologies emerging as a potential resource to address this problem. The inclusion of student input in the design and development of such interventions is critical to improving their impact. This study contributed to the initial phase of a research project that aims to adapt and evaluate the feasibility and acceptability of an early intervention for anxiety and depression based on digital technologies for university students. Three participatory workshops were conducted with 13 university students in Chile to inquire about the features and content that a mental health mobile app should include to meet their needs and preferences. The workshop transcripts were analysed using inductive thematic analysis. The results of this study highlight the value of modifications such as the personalisation of some features of the app. The students recommended incorporating topics related to university life and the possibility of contacting a mental health professional, as well as the inclusion of peer interaction or other forms of support.